Association of Endovascular Thrombectomy With Functional Outcome in Patients With Acute Stroke With a Large Ischemic Core. (27th September 2022) - Garcia-Esperon, Carlos; Bivard, Andrew; Johns, Hannah; Chen, Chushuang; Churilov, Leonid; Lin, Longting; Butcher, Kenneth; Kleinig, Timothy J.; Choi, Philip M.C.; Cheng, Xin; Dong, Qiang; Aviv, Richard I.; et al.
Abstract : Background and Objectives: Endovascular thrombectomy (EVT) is effective for patients with large vessel occlusion (LVO) stroke with smaller volumes of CT perfusion (CTP)-defined ischemic core. However, the benefit of EVT is unclear in those with a core volume >70 mL. We aimed to compare outcomes of EVT and non-EVT patients with an ischemic core volume ≥70 mL, hypothesizing that there would be a benefit from EVT for fair outcome (3-month modified Rankin scale [mRS] 0–3) after stroke. Methods: A retrospective analysis of patients enrolled into a multicenter (Australia, China, and Canada) registry (2012–2020) who underwent CTP within 24 hours of stroke onset and had a baseline ischemic core volume ≥70 mL was performed. The primary outcome was the estimation of the association of EVT in patients with core volume ≥70 mL and within 70–100 and ≥100 mL subgroups with fair outcome. Results: Of the 3, 283 patients in the registry, 299 had CTP core volume ≥70 mL and 269 complete data (135 had core volume between 70 and 100 mL and 134 had core volume ≥100 mL). EVT was performed in 121 (45%) patients. EVT-treated patients were younger (median 69 vs 75 years; p = 0.011), had lower prestroke mRS, and smaller median core volumes (92 [79–116.5] mL vs 105.5 [85.75–138] mL, p = 0.004). EVT-treated patients had higher odds of achieving fair outcome in adjusted analysis (30% vs 13.9% in the non-EVT group; adjusted odds ratio [aOR] 2.1, 95% CI 1–4.2, p = 0.038). The benefit was seen predominantly in those with 70–100 mL core volume (71/135 [52.6%] EVT-treated), with 54.3% in the EVT-treated vs 21% in the non-EVT group achieving a fair outcome (aOR 2.5, 95% CI 1–6.2, p = 0.005). Of those with a core volume ≥100 mL, 50 of the 134 (37.3%) underwent EVT. Proportions of fair outcome were very low in both groups (8.1% vs 8.7%; p = 0.908). Discussion: We found a positive association of EVT with the 3-month outcome after stroke in patients with a baseline CTP ischemic core volume 70–100 mL but not in those with core volume ≥100 mL. Randomized data to confirm these findings are required. Classification of Evidence: This study provides Class III evidence that EVT is associated with better motor outcomes 3 months after CTP-defined ischemic stroke with a core volume of 70–100 mL.